2014
DOI: 10.2196/mhealth.3216
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Technologies and Geographic Information Systems to Improve Health Care Systems: A Literature Review

Abstract: BackgroundA growing body of research has employed mobile technologies and geographic information systems (GIS) for enhancing health care and health information systems, but there is yet a lack of studies of how these two types of systems are integrated together into the information infrastructure of an organization so as to provide a basis for data analysis and decision support. Integration of data and technical systems across the organization is necessary for efficient large-scale implementation.ObjectiveThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 245 publications
(459 reference statements)
0
38
0
4
Order By: Relevance
“…Although the number of studies included in these reviews have been few in number, improvements have been observed in health care service delivery processes [10], behavior change (particularly smoking cessation) [10,11], and use of geographic information systems to support improved health care [12]. In LMIC settings, the mHealth literature is dominated by interventions in maternal and child health and sexual health, with a particular focus on use of mobile phones for data collection [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Although the number of studies included in these reviews have been few in number, improvements have been observed in health care service delivery processes [10], behavior change (particularly smoking cessation) [10,11], and use of geographic information systems to support improved health care [12]. In LMIC settings, the mHealth literature is dominated by interventions in maternal and child health and sexual health, with a particular focus on use of mobile phones for data collection [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Many SMBG meters have the capability of transmitting data and the impact on health continues to expand to address potential communication barriers between patients and clinicians [6,9,10]. The information from this pilot study adds to the body of literature to support the use of real-time SMBG data in a primary care setting to improve clinical outcomes [11][12][13].…”
Section: Discussionmentioning
confidence: 93%
“…In SaaS mode, users do not need to manage or participate in the operation of the cloud platform. Those who can more effectively 9 control the updating of data content and maintenance provide this service. In terms of the physical function of the system, data analysis and health care advice and information are transferred using the platform as a service (PaaS) model.…”
Section: Cloud Computing Architecturementioning
confidence: 99%
“…Evidence from a survey also shows that 60% of surveyed healthcare organizations fail to develop a clear, integrated enterprise strategy or a vision for the deployment of analytics across a broad range of functions [8]. One of the 2 reasons for these failures is a lack of understanding of the potential technological benefits of HIT [9,10]. However, with appropriate investment, HIT has the potential to allow healthcare organizations to harness the capabilities of databases, information and knowledge [11].…”
Section: Introductionmentioning
confidence: 99%